Pre-exposure prophylaxis awareness, use, and intention to use in a regional sample of Latin American geosocial networking application users in 2018–2019. (November 2021) - Blair, Kevin J; Segura, Eddy R; Garner, Alex; Lai, Jianchao; Ritterbusch, Amy; Leon-Giraldo, Sebastian; Guilamo-Ramos, Vincent; Lake, Jordan E; Clark, Jesse L; Holloway, Ian W
Pre-exposure prophylaxis (PrEP) access is increasing in Latin America. We explored PrEP use among Spanish-speaking, Hornet geosocial networking application users from Latin American countries with limited PrEP data via an online survey completed between December 2018 and February 2019. A total of 718 Hornet users from 10 countries were included, of whom 72.1% reported PrEP awareness. Few (5.6%) were currently taking PrEP, though 32.1% intended to take PrEP in the subsequent 6 months. PrEP awareness was lower in 18–25 year olds compared to 26+ (62.4% vs. 75.6%, aOR 0.67, [95% CI 0.46–0.97]), and higher among those living in larger versus smaller cities (74.4% vs. 58.8%, aOR 1.96, [95% CI 1.25–3.07]) or countries with at least partial versus no PrEP policy adoption (79.1% vs. 60.8%, aOR 2.20, [95% CI 1.56–3.12]). Intention to use PrEP was higher among PrEP-eligible respondents (51.8% vs. 29.6%, aOR 2.26, [95% CI 1.26–4.07]) and those recently tested for a sexually transmitted infection (35.4% vs. 25.5%, aOR 1.58, [95% CI 1.01–2.48]). Efforts to expand PrEP use in Latin America should focus on national PrEP policy adoption, and research should explore barriers to awareness and use among young men who have sex with men.